AutoCAD for engineers - Jamaludin Mohd Taib (Penerbit Universiti Teknologi Malaysia, 2012)
AutoCAD for Engineers is intended as a guide especially for Mechanical Engineers to implement AutoCAD specifically to produce engineering drawing.